Rotatividade de funcionários em uma rede de correspondentes bancários - Cavalheiro, Sabrina dos Santos (2023)
This article aims to carry out a diagnosis that can contribute to the company's employee turnover rate, thinking about a lasting future in the company, being a good place to work. As a reference, variables based on People Management (PM) are explored, which refers to people retention and turnover, with factors that influence the company. The research that underpins this work has a quantitative and descriptive approach, being based on experiences in the work environment itself and also on data collection carried out through a questionnaire designed for employees. Based on the research results, the factors that influence the company's turnover are evident, factors that are suggested as improvements to reduce this rate. It concludes that investment should be made in more benefits and career plans for employees.